GURINDAM DUA BELAS IN THE CONTEXT OF ISLAMIC VALUES - Rayhan Musa Novian; Nordiana Mohd Nordin (Journal of Islamic, Social, Economics and Development, 2023)
This study aims to get an overview of the content in Gurindam Dua Belas written by Raja Ali Haji related to the context of morals of Islamic education. Raja Ali Haji is known as a poet who comes from the Riau Islands, Indonesia. He was a member of the Malay-Bugis royal household of Riau-Lingga in the nineteenth century. He wrote Gurindam Dua Belas with twelve clauses. Each clause consists of two stanzas, and each stanza consists of two lines of sentences with the same rhyme and constitutes a unified whole. This study uses VoyantTools tool to mining the text in the Gurindam Dua Belas manuscripts to obtain comprehensive information. The focuses of text mining are on entities related to moral Islamic education. The Gurindam Dua Belas acknowledge as a message that introduces Malay cultural heritage. In the findings of the study discovered that the first chapters of Gurindam Dua Belas discussed Islamic practices and moral values. The focus is on prayer, Aqidah & Ahlaq. In this chapter, researchers conducted text mining and found several frequent keywords as guidelines to comprehend the text in the context. In this study of Raja Ali Haji thoughts that can be extracted and defined in the further significant scope of moral values and the Islamic values.